Agrotóxicos, vulnerabilidades socioambientais e saúde : uma avaliação participativa em municípios da bacia do rio Juruena, Mato Grosso - Beserra, Lucimara (2017)
The territory of Mato Grosso became strategic for a world capitalist agricultural production. This productive chain, based hegemonically on the model of production of monoculture latifundia, is chemical-dependent millions of liters of pesticides, which has been producing environmental pollution and various diseases and vulnerability processes for a population. Objective – Analyze the consumption of pesticides in agricultural production, the environmental contamination by pesticides and the protective and destructive processes in the school territory, as components of socio-environmental vulnerability in the municipalities of Campo Novo do Parecis, Sapezal and Campos de Júlio, in Mato Grosso. Methods – Based on the theoretical-methodological of Critical Epidemiology, a study was carried out with quantitative and qualitative approaches of a participatory character. The research was carried out in six schools, a rural school and an urban school in the municipalities of Campo Novo do Parecis, Sapezal and Campos de Júlio, and counted on the formation of a Conducting Group in each school, composed of students and a teacher, who accompanied and participated in the development of the research. With the Conductor Groups, a workshop was carried out to map socio-environmental vulnerability of the school territory, and water samples were collected from artesian wells and rain from the six schools. The collected samples of artesian well water and rain were analyzed for the detection of residues of pesticides by the solid phase extraction method C-18, identification and quantification in gas chromatograph coupled to mass spectrometer (GC / MS) for nine active ingredients: atrazine, lambda-cyhalothrin, α-endosulfan, β-endosulfan, malathion, metolachlor, metribuzin, permethrin, trifluralin. Results - The main processes and elements that protect life have been identified in the school territory: schools, trees and agricultural activities close to schools, food production and generation of jobs. However, planting areas close to schools, due to the use of pesticides, was the destructive process to life listed predominantly in all maps. In the artesian well samples, atrazine (0.12 μg/L to 0.28 μg/L) and metolachlor (0.34 μg/L to 0.63 μg/L) were detected in four artesian wells of the six wells analyzed. In the rain samples 55% presented residues of at least one type of pesticide among five detected ones (metolachlor, atrazine, trifluralin, malationa and metribuzim), with metolachlor having the highest detection frequency (86%) among the positive samples. Conclusions - The results of the analyzes in environmental samples demonstrate the water and atmospheric components of the ecosystems in the municipalities are contaminated by pesticides. The protective and destructive elements and processes mapped in the school territory, as well as the contaminations evidenced in the rain and water of artesian wells, compose the relationships and processes of social and environmental vulnerability of the populations of these municipalities, being relevant for the attention and performance of the Surveillance in Health in these territories.